Autofluorescence bronchoscopy for lung cancer surveillance based on risk assessment. Issue 4 (13th November 2006) - Loewen, Gregory; Natarajan, Nachimuthu; Tan, Dongfeng; Nava, Enriqueta; Klippenstein, Donald; Mahoney, Martin; Cummings, Michael; Reid, Mary
Abstract : Background: This is a preliminary report of an ongoing prospective bimodality lung cancer surveillance trial for high-risk patients. Bimodality surveillance incorporates autofluorescence bronchoscopy (AFB) and spiral CT (SCT) scanning in high-risk patients as a primary lung cancer surveillance strategy, based entirely on risk factors. AFB was used for surveillance and findings were compared with conventional sputum cytology for the detection of malignancy and pre-malignant central airway lesions. Methods: 402 patients registering at Roswell Park Cancer Institute were evaluated with spirometric testing, chest radiography, history and physical examination, of which 207 were deemed eligible for the study. For eligibility, patients were required to have at least two of the following risk factors: (1) ⩾20 pack year history of tobacco use, (2) asbestos-related lung disease on the chest radiograph, (3) chronic obstructive pulmonary disease with a forced expiratory volume in 1 s (FEV1 ) <70% of predicted, and (4) prior aerodigestive cancer treated with curative intent, with no evidence of disease for >2 years. All eligible patients underwent AFB, a low-dose SCT scan of the chest without contrast, and a sputum sample was collected for cytological examination. Bronchoscopic biopsy findings were correlated with sputum cytology results, SCT-detected pulmonary nodules and surveillance-detected cancers. To date, 186 have been enrolled with 169 completing the surveillance procedures. Results: Thirteen lung cancers (7%) were detected in the 169 subjects who have completed all three surveillance studies to date. Pre-malignant changes were common and 66% of patients had squamous metaplasia or worse. Conventional sputum cytology missed 100% of the dysplasias and 68% of the metaplasias detected by AFB, and failed to detect any cases of carcinoma or carcinoma-in-situ in this patient cohort. Sputum cytology exhibited 33% sensitivity and 64% specificity for the presence of metaplasia. Seven of 13 lung cancers (58%) were stage Ia or less, including three patients with squamous cell carcinoma. Patients with peripheral pulmonary nodules identified by SCT scanning of the chest were 3.16 times more likely to exhibit pre-malignant changes on AFB (p<0.001). Conclusion: Bimodality surveillance will detect central lung cancer and pre-malignancy in patients with multiple lung cancer risk factors, even when conventional sputum cytology is negative. AFB should be considered in high-risk patients, regardless of sputum cytology findings.